Respuesta :
Answer:
The simplified form of expression (-2 - 8x) + (-4x - 10) is
-12(x + 1)
Step-by-step explanation:
It is given an expression (-2 - 8x) + (-4x - 10)
To find the simplified expression of (-2 - 8x) + (-4x - 10)
Let expression is given by
(-2 - 8x) + (-4x - 10) = -2 - 8x -4x -10
= -2 -10 -4x -8x
= -12 -12x
-12(x + 1) (since -12 is common in both terms)
Therefore simplified form is -12(x + 1)
Answer:
The answer is -12x - 12
Step-by-step explanation:
-2 - 8x - 4x - 10
= -2 + -8x + -4x + -10
Combine like terms:
-2 + -8x + -4x + -10
(-8x + -4x) + (-2 + -10)
= -12x + -12
= -12x - 12